2017
DOI: 10.22266/ijies2017.0831.13
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Scheme for Orthogonal Frequency Division Multiplexing-Radio over Fiber Based on Modulator and Dithering Technique: Impact of Self Phase Modulation and Group Velocity Dispersion

Abstract: Nonlinearity characteristic in OFDM (Orthogonal Frequency Division Multiplexing)-RoF (Radio over Fiber) system which causes the frequency shift of light and has a high electrical field on medium transmission. We begin by discussing SPM (Self Phase Modulation) and GVD (Group Velocity Dispersion) are part of nonlinear characteristic. SPM induced spectral broadening will be degrade performance of light wave and GVD will be impact on duration pulse of optic. The impaired information signal reduces the power and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…That is intresting problem to research. In [10] the research showed also contellation diagram based on dithering and processing signal. This papepr will develop and detail focus in nosie charateristic reduce on nonlinear condition.…”
Section: Introductionmentioning
confidence: 99%
“…That is intresting problem to research. In [10] the research showed also contellation diagram based on dithering and processing signal. This papepr will develop and detail focus in nosie charateristic reduce on nonlinear condition.…”
Section: Introductionmentioning
confidence: 99%